Myocilin Gene Mutation Induced Autophagy Activation Causes Dysfunction of Trabecular Meshwork Cells - Yan, Xuejing; Wu, Shen; Liu, Qian; Cheng, Ying; Zhang, Jingxue; Wang, Ningli (Frontiers in Cell and Developmental Biology, 2022)
Trabecular meshwork dysfunction is the main cause of primary open angle glaucoma (POAG) associated with elevated intraocular pressure (IOP). Mutant myocilin causes glaucoma mainly via elevating IOP. Previously we have found that accumulated Asn 450 Tyr (N450Y) mutant myocilin impairs human trabecular meshwork (TM) cells by inducing chronic endoplasmic reticulum (ER) stress response in vitro. However, it is unclear how ER stress leads to TM damage and whether N450Y myocilin mutation is associated with POAG in vivo. Here we found that N450Y mutant myocilin induces autophagy, which worsens cell viability, whereas inhibition of autophagy increases viability and decreases cell death in human TM cells. Furthermore, we construct a transgenic mouse model of N450Y myocilin mutation (Tg-MYOCN450Y) and Tg-MYOCN450Y mice exhibiting glaucoma phenotypes: IOP elevation, retinal ganglion cell loss and visual impairment. Consistent with our published in vitro studies, mutant myocilin fails to secrete into aqueous humor, causes ER stress and actives autophagy in Tg-MYOCN450Y mice, and aqueous humor dynamics are altered in Tg-MYOCN450Y mice. In summary, our studies demonstrate that activation of autophagy is correlated with pathogenesis of POAG.